Lulu walks the dogs - Viorst, Judith (Atheneum Books for Young Readers, 2012)
Lulu needs help from a boy named Fleischman if she is to earn money walking her neighbors' dogs, and she finds out that if she wants her business venture to succeed, she has to be nice.